ANALISIS PENDAPATAN USAHA TERNAK DOMBA KISAR YANG DIPELIHARA SECARA SEMI INTENSIF DI PULAU KISAR PROVINSI MALUKU - Maukenu, Maikel B; Tulalessy, Abraham H.; Tatipikalawan, Jomima M.; Tomatala, G. S. J. (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2024)
The purpose of this study is to find out the amount of income and its contribution to the household income of Kisar sheep farmers and the factors that affect the income of Kisar sheep livestock business. The method of sampling the area by purposive sampling is to have the largest population of Kisar Sheep on Kisar Island, namely South Kisar District and North Kisar District, Southwest Maluku Regency. Each sub-district consists of 2 villages. A total of 60 farmer respondents were taken based on the criteria of having raised Ground Sheep for at least 3 years, using a semi-intensive system and having done marketing. Descriptive data analysis, economic calculations, income contribution and multiple regression analysis to see the factors that affect income from the Kisar Sheep livestock business. The results of the study show that explicitly the income of the Kisar Sheep livestock business is Rp. 25,335,789.34 per year and explicitly and implicitly of Rp. 8,454,643.67 per year. The contribution of income from the Kisar Sheep livestock business to the total family income is 28.95%. Factors that affect the income of the Sheep Grazing business are livestock ownership, the number of livestock marketed and the selling price at the livestock level.